Changes in temperature sensitivity of spring phenology with recent climate warming in Switzerland are related to shifts of the preseason. (6th July 2017) - Güsewell, Sabine; Furrer, Reinhard; Gehrig, Regula; Pietragalla, Barbara
Abstract: The spring phenology of plants in temperate regions strongly responds to spring temperatures. Climate warming has caused substantial phenological advances in the past, but trends to be expected in the future are uncertain. A simple indicator is temperature sensitivity, the phenological advance statistically associated with a 1°C warmer mean temperature during the "preseason", defined as the most temperature‐sensitive period preceding the phenological event. Recent analyses of phenological records have shown a decline in temperature sensitivity of leaf unfolding, but underlying mechanisms were not clear. Here, we propose that climate warming can reduce temperature sensitivity simply by reducing the length of the preseason due to faster bud development during this time period, unless the entire preseason shifts forward so that its temperature does not change. We derive these predictions theoretically from the widely used "thermal time model" for bud development and test them using data for 19 phenological events recorded in 1970–2012 at 108 stations spanning a 1600 m altitudinal range in Switzerland. We consider how temperature sensitivity, preseason start, preseason length and preseason temperature change (i) with altitude, (ii) between the periods 1970–1987 and 1995–2012, which differed mainly in spring temperatures, and (iii) between two non‐consecutive sets of 18 years that differed mainly in winter temperatures. On average, temperature sensitivity increased with altitude (colder climate) and was reduced in years with warmer springs, but not in years with warmer winters. These trends also varied among species. Decreasing temperature sensitivity in warmer springs was associated with a limited forward shift of preseason start, higher temperatures during the preseason and reduced preseason length, but not with reduced winter chilling. Our results imply that declining temperature sensitivity can result directly from spring warming and does not necessarily indicate altered physiological responses or stronger constraints such as reduced winter chilling. Abstract : Model for possible changes in the temperature sensitivity of spring phenology with climate warming if the start date t0 of temperature‐driven bud ontogenesis (preseason) gets delayed. The later start date and higher daily temperatures lead to faster bud development, reducing preseason length. The end date of the preseason (average onset date t ¯ 1 ) only slightly shifts forward due to the later start, causing the temperature at preseason end to be higher. These changes are predicted to result in reduced temperature sensitivity.